Utilization of Artificial Intelligence in Making Learning Materials Easier and More Innovative at SMA and SMK Syakhyakirti Palembang: Pemanfaatan Artificial Intelligence Dalam Membuat Bahan Ajar Yang Lebih Mudah dan Inovatif di SMA dan SMK Syakhyakirti Palembang - Purwita Sari; Sutarno, Sutarno; Rossi Passarella; Rahmat Fadli Isnanto; Dedy Kurniawan; Huda Ubaya; Ahmad Rifai; Kemahyanto Exaudi (Universitas Lancang Kuning, 2025)
The use of Artificial Intelligence (AI) in developing teaching materials at SMA and SMK Syakhyakirti Palembang provides convenience and introduces new innovations in the field of education. AI is a technology with tremendous potential to improve the quality of education by offering interactive, engaging, and relevant teaching materials tailored to students' needs. In this study, data was collected through interviews with teachers, observations of the learning process, and analysis of teaching materials created with the assistance of AI technology. The results of the study show that AI can enhance efficiency in the creation of teaching materials, provide a broader range of content, and enable customization of materials based on students' abilities and interests. Additionally, AI supports teachers in monitoring students' learning progress through more accurate and structured data analysis. By implementing this technology, the learning process at SMA and SMK Syakhyakirti Palembang has become more effective, modern, and innovative. This study also provides important recommendations, including training for teachers in the use of AI, the development of supportive technological infrastructure, and strategies for integrating AI into teaching practices. These efforts are expected to be adopted by other educational institutions to foster sustainable improvements in the quality of education.